ANALISIS KEBERLANGSUNGAN USAHA PEMBENIHAN UDANG PT.SWADAYA MITRA PERKASA DI DESA LUK KECAMATAN RHEE KABUPATEN SUMBAWA TAHUN 2023 - Aprirachman, Rozzy; Merliana, Dinda (Jurnal Nusa Manajemen, 2024)
This research was conducted with the aim of determining the level of business sustainability of PT. Swadaya Mitra Perkasa located in Luk Village, Rhee District, Sumbawa Regency. Companies that act as shrimp seed producers already have a wide market. PT. Swadaya Mitra Perkasa has a product called "Benur TOP". This research uses composite index analysis with MSI to see the level of business sustainability from 3 dimensions, namely economic, social and environmental dimensions. The population in the study consisted of 30 respondents obtained based on the Slovin sampling technique. The results of this research show that the overall economic dimension has a high business sustainability value, where the composite index value is > 0.68. while in the social dimension there is 1 indicator with a moderate business sustainability value. Namely the education indicator, where the educational background of PT employees. Swadaya Mitra Perkasa varies from elementary, middle school, high school, vocational school, D2 and S1 education levels. Then, in the environmental dimension, there is 1 indicator with a moderate sustainability value, namely appropriate pond model and construction. so it can be concluded in this research that the business sustainability of PT. Swadaya Mitra Perkasa is of high value.